2015
DOI: 10.1002/cphc.201500164
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Hydrogen Bonds Enhance Disparity in Reactivity between Isomers of Photoswitchable Sorbents and CO2: A Computational Study

Abstract: Reducing the emission of greenhouse gases, such as CO2 , requires efficient and reusable capture materials. The energy for regenerating sorbents is critical to the cost of CO2 capture. Here, we design a series of photoswitchable CO2 capture molecules by grafting Lewis bases, which can covalently bond CO2 , to azo-based backbones that can switch configurations upon light stimulation. The first-principles calculations demonstrate that intramolecular hydrogen bonds are crucial for enlarging the difference of CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In recent years, in addition to the capture and storage technology [1][2][3][4][5][6][7], the recycling technology for CO2, a major greenhouse gas, has attracted considerable interest. A promising route for relieving the greenhouse effect is to convert CO2 into CO, which has been widely investigated in the recycling technology.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in addition to the capture and storage technology [1][2][3][4][5][6][7], the recycling technology for CO2, a major greenhouse gas, has attracted considerable interest. A promising route for relieving the greenhouse effect is to convert CO2 into CO, which has been widely investigated in the recycling technology.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] It is well-known that anionic NHCs (non-carbenes) dominate the reactions with CO 2 , while the charge balancing cations only exhibit limited secondary effects. 4,15,[21][22][23][24][25][26][27] However, in some cases, the cation effects are indispensable. Very recent experiments by He and Dai groups have revealed that the weakly basic salts composed of lithium or potassium and organic bases can nearly 1 : 1 stoichiometrically react with CO 2 by forming stable zwitterionic carbamate adducts through multidentate coordination between the metal cation and organic base.…”
Section: Introductionmentioning
confidence: 99%
“…For an example, Tang et al [70] had utilised AZB as the base in the backbones in conjunction with Lewis bases by covalently bonding them to design novel photo-switchable sorbents for CO 2 capture. Results demonstrated that the difference in binding strength between the designed molecules and CO 2 was hardly affected by electronic and steric effects.…”
Section: Systemsmentioning
confidence: 99%